Type 2 diabetes mellitus and bone. (8th January 2018) - Compston, J.
Abstract: Type 2 diabetes (T2DM) is a rapidly growing public health problem. It is associated with an increased risk of fracture, particularly of the hip, despite normal or high bone mineral density. Longer duration of disease and poor glycaemic control are both associated with higher fracture risk. The factors underlying increased fracture risk have not been clearly established, but increased falls risk, obesity, sarcopenia and co‐morbidities are likely to contribute. The basis for reduced bone strength despite higher bone mineral density remains to be fully elucidated. Bone turnover is reduced in individuals with T2DM, with evidence of impaired bone formation. Most studies indicate normal or superior trabecular bone structure although reduced lumbar spine trabecular bone score (TBS) has been reported. Deficits in cortical bone structure have been demonstrated in some, but not all, studies whilst reduced bone material strength index (BMSi), as assessed by microindentation, has been a consistent finding. Accumulation of advanced glycation end products in bone may also contribute to reduced bone strength. The use of FRAX in individuals with T2DM underestimates fracture probability. Clinical management should focus on falls prevention strategies, avoidance of known risk factors, maintenance of good glycaemic control and bone protective intervention in individuals at high risk of fracture. Dietary and surgical strategies to reduce weight have beneficial effects on diabetes but may have adverse effects on skeletal health. Future research priorities include better definition of the mechanisms underlying increased fracture risk in T2DM and optimal strategies for identifying and treating those at high risk.